Narrazione e psicoanalisi. Quale modello di narrazione? - Paolo Francesco Pieri (Aisthesis, 2012)
The essay sheds light on the centrality of fiction and narration in the pattern of psychoanalytic relationship. The passage from a medically centered clinical relation to a critical psychotherapy entails a renunciation to any presumption of a universal subjectivity. The subject of such analysis is given just by the construction of a resurgent existential texture in which the fiction and narration  activity plays a prominent role.